Understanding wage restraint in the German public sector: does the pattern bargaining hypothesis really hold water? - Donato Di Carlo (Industrial Relations Journal, 2020)
German public sector wage restraint has been explained through the presence of a specific type of inter-sectoral wage coordination in the industrial relations system—that is, export sector-led pattern bargaining. First, as a literature-assessing exercise, this paper reviews the literature in industrial relations and comparative political economy (CPE) and finds that (i) the origins and mechanics of inter-sectoral wage coordination through pattern bargaining have never been laid out clearly; (ii) that the mechanisms of the pattern bargaining thesis have never been tested empirically; and (iii) that the CPE literature reveals an export-sector bias. Second, as a theory-testing exercise, hoop tests are performed to verify the pattern bargaining hypothesis. The key finding is that Germany cannot be considered a case of export sector-driven pattern bargaining, opening a new research agenda for the study of public sector wage setting centred on public sector employment relations, public finance, public administrations and the politics of fiscal policy.
Keywords: 330